RETRACTED: AI as driver of intellectual transport infrastructure ecosystem: Current issues - Drozdova Maria; Berezovskaya Irina; Shipunova Olga (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 138, 00001 (2024), https://doi.org/10.1051/bioconf/202413800001